Pengaruh Senam Ergonomik terhadap Nyeri Rematik pada Lansia - Maura, Salsa Bila Siva; Tresya, Elvie; Agustina, Marisca (Journal of Nursing Education and Practice, 2024)
Introduction: Rheumatic pain is pain caused by inflammation in swollen joints, inflammation or damage has occurred that causes pain. Doing ergonomic gymnastics can reduce the risk and manage rheumatic pain, namely through relaxation exercises, the elderly are directed to relax and be able to reach a calm state, and can reduce pain in the joints for the elderly who experience joint problems.      Objectives: To determine the effect of ergonomic gymnastics on rheumatic pain in the elderly in Leuwinanggung Village RT 02 RW 010 in 2022. Method: This research is quantitative research with a Quasi-Experimental research design with one group pre-test post-test design. The population in this study was the elderly in Leuwinanggung Village who experienced rheumatic pain as many as 64 elderly people. Sampling technique with random sampling and a sample of 20 respondents. Data collection instruments using numeric rating scale (NRS) pain measurement questionnaire sheets were then carried out normality tests with the Shapiro Wilk test and influence tests using the Wilcoxon Test. Result: Based on the results of the Wilcoxon test on the effect of ergonomic gymnastics on rheumatic pain in the elderly, a p-value of 0.002 < 0.05 was obtained. Conclusion: There is an influence of ergonomic gymnastics on rheumatic pain in the elderly in Leuwinanggung Village RT 02 RW 010 in 2022.